Influenza Vaccine Effectiveness by A(H3N2) Phylogenetic Subcluster and Prior Vaccination History: 2016–2017 and 2017–2018 Epidemics in Canada. (26th March 2020) - Skowronski, Danuta M; Leir, Siobhan; Sabaiduc, Suzana; Chambers, Catharine; Zou, Macy; Rose, Caren; Olsha, Romy; Dickinson, James A; Winter, Anne-Luise; Jassem, Agatha; Gubbay, Jonathan B; Drews, Steven J; et al.
Abstract: Background: The influenza A(H3N2) vaccine was updated from clade 3C.3a in 2015–2016 to 3C.2a for 2016–2017 and 2017–2018. Circulating 3C.2a viruses showed considerable hemagglutinin glycoprotein diversification and the egg-adapted vaccine also bore mutations. Methods: Vaccine effectiveness (VE) in 2016–2017 and 2017–2018 was assessed by test-negative design, explored by A(H3N2) phylogenetic subcluster and prior season's vaccination history. Results: In 2016–2017, A(H3N2) VE was 36% (95% confidence interval [CI], 18%–50%), comparable with (43%; 95% CI, 24%–58%) or without (33%; 95% CI, −21% to 62%) prior season's vaccination. In 2017–2018, VE was 14% (95% CI, −8% to 31%), lower with (9%; 95% CI, −18% to 30%) versus without (45%; 95% CI, −7% to 71%) prior season's vaccination. In 2016–2017, VE against predominant clade 3C.2a1 viruses was 33% (95% CI, 11%–50%): 18% (95% CI, −40% to 52%) for 3C.2a1a defined by a pivotal T135K loss of glycosylation; 60% (95% CI, 19%–81%) for 3C.2a1b (without T135K); and 31% (95% CI, 2%–51%) for other 3C.2a1 variants (with/without T135K). VE against 3C.2a2 viruses was 45% (95% CI, 2%–70%) in 2016–2017 but 15% (95% CI, −7% to 33%) in 2017–2018 when 3C.2a2 predominated. VE against 3C.2a1b in 2017–2018 was 37% (95% CI, −57% to 75%), lower at 12% (95% CI, −129% to 67%) for a new 3C.2a1b subcluster (n = 28) also bearing T135K. Conclusions: Exploring VE by phylogenetic subcluster and prior vaccination history reveals informative heterogeneity. Pivotal mutations affecting glycosylation sites, and repeat vaccination using unchanged antigen, may reduce VE. Abstract : During 2016–2017 and 2017–2018 influenza A(H3N2) epidemics, updated clade 3C.2a vaccine bore egg-adaptation mutations and circulating 3C.2a viruses showed substantial genetic diversity. Vaccine effectiveness by phylogenetic subcluster and prior vaccination history reveal informative heterogeneity underpinning subtype-specific findings.